Mall Mania in India: Changing Consumer Shopping Habits - Taneja, Kanika (2007)
For the current generation of consumers, the meaning of shopping has changed. It is not just a mere necessity, as it was earlier, but much more than that. The factors that affect store choice and draw customers to the shopping centre include space, ambience, and convenience and moreover an array of choice under one roof. The growth of integrated shopping malls, retail chains and multi-brand outlets is evidence of consumer behaviour being favourable to the growing organized segment of the business. Space, ambience and convenience are beginning to play an important role in drawing customers. Malls, which are now anchored by large outlets such as Westside and Lifestyle and are resided by a lot of Indian and international brands, are also being seen as image benchmarks for communities. Thus, this dissertation aims at studying the changing shopping trends of consumers in the Indian economy. For doing this, semi structured interviews from the Indian retailers as well as consumers have been used as a tool. Various factors on which the Indian consumers base their choice of going to the shopping mall or the unorganized markets have been analyzed in this research.